Predictors of review sites usage in hotels - Perez-Aranda, Javier (2017)
The tourism industry has being strongly impacted by the consumer use of review sites. Since review sites such as TripAdvisor allowed accommodations to create own profiles with information, hotels began incorporating these actions into their engaging customers programming. Despite the benefits that review sites can offer to customers, hotels and accommodations, its implementation is not developed and exploited in all its possibilities, and little is known about hotels use of this review sites. This study explores the topic trough quantitative methodology, conducting multiple correlation analysis of data obtained from a sample of 301 hotel managers. Managers consider they are committed to this type of platforms and are capable of use it accurately. Also, we find evidence of correlation between use of TripAdvisor and hotel characteristics (size, ownership structure, and category). Furthermore, multiple regression analysis shows competence and commitment as the most important predictors of use intensity.